Carbon starvation increases endoglycosidase activities and production of "unconjugated N-glycans" in Silene alba cell-suspension cultures. - Lhernould, S (1994)
We previously reported the occurrence of oligomannosides and xylomannosides corresponding to unconjugated N-glycans (UNGs) in the medium of a white campion (Silene alba) cell suspension. Attention has been focused on these oligosaccharides since it was shown that they confer biological activities in plants. In an attempt to elucidate the origin of these oligosaccharides, we studied two endoglycosidase activities, putative enzymes involved in their formation. The previously described peptide-N4-(N-acetyl-glucosaminyl) asparagine amidase activity and the endo-N-acetyl-beta-D-glucosaminidase activity described in this paper were both quantified in white campion cells during the culture cycle with variable initial concentrations of sucrose. The lower the sucrose supply, the higher the two activities. Furthermore, endoglycosidase activities were greatly enhanced after the disappearance of sugar from the medium. The production of UNGs in the culture medium rose correlatively. These data strongly suggest that the production of UNGs in our white campion cell-suspension system is due to the increase of these endoglycosidase activities, which reach their highest levels of activity during conditions of carbon starvation.